A positive electrode material and preparation method thereof, secondary battery and electrical equipment
By using a cladding layer composed of Li3PO4, B2O3 and LiF in the positive electrode material of ternary lithium-ion batteries, the problem of poor structural stability is solved and the cycle life and performance of the battery is improved.
Patent Information
- Application Number
- CN202411018035.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-29
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-07-29
AI Technical Summary
The existing ternary lithium-ion battery positive electrode material has poor structural stability, resulting in a short battery cycle life.
Using a positive electrode material including a core and a cladding layer, the core consists of ternary positive electrode active substances, and the cladding layer consists of Li3PO4, B2O3 and LiF. It forms a fast ion conductor migration channel by adapting the cladding layer to reduce side reactions and lithium ions. Consumption, improve cycle stability.
It improves the discharge capacity, cycle stability and rate performance of the material, extends the cycle life of the battery, and reduces the occurrence of side reactions.
Smart Images

Figure CN118553896B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion battery manufacturing, and in particular to a positive electrode material and a preparation method thereof, a secondary battery and an electrical device. Background Art
[0002] At present, ternary lithium batteries have received widespread attention due to the advantages of ternary positive electrode materials such as high energy density and green and pollution-free.
[0003] However, the existing positive electrode materials of ternary lithium batteries have irreversible structural phase changes, transition metal dissolution, and interfacial side reactions between the electrolyte and the positive electrode materials, which affect the cycle life and thermal stability of the materials. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a positive electrode material and a preparation method thereof, a secondary battery and an electrical device to improve the problem that the positive electrode material of the existing ternary lithium-ion battery has poor structural stability, resulting in a short battery cycle life.
[0005] In order to improve the above problems, the present invention is achieved through the following technical solutions:
[0006] The present invention provides a positive electrode material, wherein the positive electrode material comprises a core and a coating layer arranged on the surface of the core, the core comprises a ternary positive electrode active material, and the coating layer comprises aLi3PO4·bB2O3·cLiF, wherein a+b+c=1, and 0 <a、b、c<1。
[0007] Furthermore, in the positive electrode material, the coating layer also includes a fluorine-containing lithium salt, and the fluorine-containing lithium salt includes LiBF4 and / or LiPF6.
[0008] Furthermore, in the positive electrode material, the ternary positive electrode active material includes LiNi x Co y A z O2, wherein A is selected from one or more of Mn and Al, x+y+z=1, and 0 <x、y、z<1。
[0009] Furthermore, in the positive electrode material, the mass ratio of the coating layer to the core is 0.5~3:100.
[0010] Furthermore, in the positive electrode material, the fluorine-containing lithium salt accounts for 5wt% to 20wt% of the total amount of the coating agent.
[0011] The present invention also provides a method for preparing a positive electrode material, comprising:
[0012] The ternary positive electrode active material is mixed with Li3PO4, B2O3 and LiF in a solvent and then dried to obtain a dry body; wherein the molar ratio of Li3PO4, B2O3 and LiF is 0~1:0~1:0~1;
[0013] The dried body is sintered in a protective gas atmosphere to obtain a positive electrode material.
[0014] Furthermore, in the preparation method, the sintering temperature is 300° C. to 600° C., and the sintering time is 1 h to 10 h.
[0015] Furthermore, in the preparation method, the ternary positive electrode active material is mixed with Li3PO4, B2O3 and LiF in a solvent and then dried, comprising:
[0016] The ternary positive electrode active material is a ternary polycrystalline positive electrode material. The ternary polycrystalline positive electrode material is mixed with Li3PO4, B2O3 and LiF, and then the solvent is added, and the mixture is optionally crushed and then dried.
[0017] Furthermore, in the preparation method, the particle size D50 of the ternary polycrystalline positive electrode material is 5.0 μm to 15.0 μm.
[0018] Furthermore, in the preparation method, the ternary positive electrode active material is mixed with Li3PO4, B2O3 and LiF by using a solvent and then dried, comprising:
[0019] The ternary positive electrode active material is a ternary single crystal positive electrode material. The ternary single crystal positive electrode material and Li3PO4, B2O3, and LiF are added to a solvent at 60°C to 100°C for treatment for 0.5h to 5h, and then the drying treatment is performed at 60°C to 100°C.
[0020] Furthermore, in the preparation method, the particle size D50 of the ternary single crystal positive electrode material is 2.0 μm to 5.0 μm.
[0021] The present invention also proposes a secondary battery, comprising a positive electrode plate, wherein the positive electrode plate comprises a positive electrode collector and a positive electrode active material layer arranged on the positive electrode collector, and the positive electrode active material layer comprises the positive electrode material as described above or the positive electrode material prepared by the above preparation method.
[0022] The present invention further provides an electric device, which includes the above-mentioned secondary battery, and the secondary battery serves as a power supply for the electric device.
[0023] Compared with the prior art, the embodiments of the present invention have the following advantages:
[0024] In the embodiments of the present invention, the provided positive electrode material includes a core and a coating layer provided on the surface of the core. The core includes a ternary positive electrode active material, and the coating layer includes aLi3PO4·bB2O3·cLiF, where a + b + c = 1, and 0 < a, b, c < 1. Among them, using Li3PO4, B2O3, and LiF to adaptively coat the ternary positive electrode active material as the coating layer can not only form a fast ion conductor migration channel on the surface of the ternary positive electrode active material, thereby improving the discharge capacity, cycle stability, and rate performance of the material; but also supplement the consumption of lithium ions, passivate the SEI film, and isolate the direct contact between the positive electrode material and the electrolyte, thereby reducing the occurrence of side reactions and improving the long-cycle performance of the material. Therefore, the positive electrode material provided in the embodiments of the present invention solves the problem that the structural stability of the positive electrode material of the existing ternary lithium-ion battery is poor, resulting in a short cycle life of the battery.
[0025] It should be understood that the above general description and the following detailed description are only exemplary and explanatory, and cannot limit this application. Description of the Drawings
[0026] Figure 1 is a schematic structural diagram of the positive electrode material provided in the embodiments of the present invention;
[0027] Figure 2-1 to Figure 2-4 are SEM scanning electron microscope images of the positive electrode materials of Examples 1, 9, 10 and Comparative Example 1 of the present invention respectively;
[0028] Figure 3 is a test comparison chart of the cycle capacity retention rate and DCIR growth of the batteries in Examples 1, 9, 10 and Comparative Example 1 of the present invention;
[0029] Figure 4 is a test comparison chart of the long-cycle gas production of the batteries in Examples 1, 9, 10 and Comparative Example 1 of the present invention;
[0030] Figure 5 is a comparison chart of the discharge capacities of the batteries in Examples 1, 9, 10 and Comparative Example 1 of the present invention at different upper limit voltages at room temperature;
[0031] Figure 6 is a test comparison chart of the high-temperature storage performance of the batteries in Examples 1, 9, 10 and Comparative Example 1 of the present invention.
[0032] Description of the Reference Numerals:
[0033] 11 - Core, 12 - Coating layer. Detailed Embodiments
[0034] To make the above objects, features, and advantages of the present invention more obvious and understandable, the present invention will be further described in detail below with reference to the drawings and specific embodiments.
[0035] The present invention provides a positive electrode material, such as Figure 1 As shown, the positive electrode material includes a core 11 and a coating layer 12 disposed on the surface of the core 11, the core 11 includes a ternary positive electrode active material, and the coating layer 12 includes aLi3PO4·bB2O3·cLiF, wherein a+b+c=1, and 0 <a、b、c<1。
[0036] In the embodiment of the present application, the ternary positive electrode active material includes a ternary polycrystalline positive electrode material and / or a ternary single crystal positive electrode material. 2- The strong PO covalent bond contained in the cathode material can prevent the release of lattice oxygen during the charge and discharge process, isolate the ternary cathode active material and the electrolyte, improve the interface stability, inhibit the occurrence of side reactions, stabilize the layered structure of the multi-material crystal, and form a fast ion coating layer on the surface of the material, thereby improving the ionic and electronic conductivity of the battery system and improving the stability of the material and the battery system; B2O3 also has a protective effect on the ternary cathode active material, which can isolate the contact between the ternary cathode active material and the electrolyte, effectively reduce the occurrence of side reactions, and achieve the effect of increasing capacity; and the inorganic lithium salt LiF is one of the main components of the SEI film of lithium-ion batteries. Adding a certain amount of LiF to the cathode material can not only passivate the SEI film and inhibit the decomposition of the electrolyte, but also reduce the consumption of lithium source during formation, and improve the cycle performance of the battery. In addition, setting a coating layer outside the ternary cathode active material can effectively reduce the risk of cracks and cracks forming inside the particles caused by repeated contraction of the unit cell, and improve the stability of the lattice structure.
[0037] Therefore, the use of Li3PO4, B2O3 and LiF to adapt and coat the ternary positive electrode active material can not only form a fast ion conductor migration channel on the surface of the ternary positive electrode active material, thereby improving the discharge capacity, cycle stability and rate performance of the material; it can also replenish the consumption of lithium ions, passivate the SEI film, and isolate the direct contact between the positive electrode material and the electrolyte, thereby reducing the occurrence of side reactions and improving the long-cycle performance of the material. Therefore, the positive electrode material provided by the embodiment of the present invention improves the problem that the structural stability of the positive electrode material of the existing ternary lithium-ion battery is poor, resulting in a short battery cycle life.
[0038] In practical applications, by performing TEM-SAED characterization on the positive electrode material provided in the embodiment of the present invention, it is shown that the surface material has a crystal structure different from that of the ternary positive electrode active material; at the same time, by using SEM-EDS to characterize the surface material, the elemental composition and ratio of Li3PO4, B2O3 and LiF can be determined, and combined with the crystal structure of the surface material characterized by TEM-SAED characterization, the presence of Li3PO4, B2O3 and LiF in the surface material can be determined.
[0039] Optionally, a:b:c = (1 to 10):(1 to 10):(1 to 10), which can not only make the matching of Li3PO4, B2O3 and LiF more reasonable, but also form a fluorine-containing lithium salt LiBF4 and / or LiPF6 with appropriate content through element rearrangement.
[0040] In the embodiment of the present invention, the ternary cathode active material includes LiNi x Co y A z O2, where A is selected from one or more of Mn and Al, x + y + z = 1, and 0 < x, y, z < 1. That is, the ternary cathode active material can be lithium nickel cobalt manganate, lithium nickel cobalt aluminate, or lithium nickel cobalt manganese aluminate. It not only has a relatively high energy density but is also more suitable for the combined coating of Li3PO4, B2O3 and LiF to form a more stable fast ion conductor migration channel.
[0041] Optionally, in one embodiment, the mass ratio of the coating layer to the core is 0.5 to 3:100, that is, the mass of the coating layer can be 0.5% to 3% of the mass of the core, which can effectively balance the ion conduction performance and energy density of the material. Optionally, the mass ratio of the coating layer to the core is any value of 0.5:100, 1:100, 2:100, 3:100 or the range value of any two of them.
[0042] Optionally, in one embodiment, the coating layer further includes a fluorine-containing lithium salt, and the fluorine-containing lithium salt includes LiBF4 and / or LiPF6. Incorporating LiBF4 and LiPF6 into the coating layer is not only beneficial to the conduction of lithium ions but also more suitable for the charge and discharge of the battery in a low-temperature environment, thereby improving the low-temperature performance of the battery.
[0043] Optionally, in one embodiment, the fluorine-containing lithium salt accounts for 5wt% to 20wt% of the total amount of the coating agent, which can effectively improve the charge and discharge performance of the battery in a low-temperature environment on the premise of effectively isolating the ternary cathode active material from the electrolyte and passivating the SEI film. Optionally, the fluorine-containing lithium salt accounts for one of 5wt%, 6wt%, 8wt%, 10wt%, 15wt%, 20wt% of the total amount of the coating agent or the range value of any two of them.
[0044] Optionally, the content of LiBF4 in the fluorine-containing lithium salt is 50wt% to 80wt%, and the content of LiPF6 in the fluorine-containing lithium salt is 20wt% to 50wt%.
[0045] The embodiment of the present invention also provides a preparation method of a cathode material, which includes steps 201 to 202:
[0046] Step 201: Evenly mix the ternary positive electrode active material with Li3PO4, B2O3 and LiF in a solvent and then dry the mixture to obtain a dried product; wherein the molar ratio of Li3PO4, B2O3 and LiF is 0~1:0~1:0~1.
[0047] In step 201, Li3PO4, B2O3 and LiF are evenly distributed on the surface of the ternary positive electrode active material by using a solvent, and then Li3PO4, B2O3 and LiF are simply coated on the surface of the ternary positive electrode active material through drying.
[0048] Step 202: Sinter the dried body in a protective gas atmosphere to obtain a positive electrode material.
[0049] In step 202, by sintering the above-mentioned ternary positive electrode active material whose surface is simply coated with Li3PO4, B2O3 and LiF in a protective gas atmosphere, a strong coating layer composed of Li3PO4, B2O3 and LiF can be formed. The coating layer can not only form a fast ion conductor migration channel on the surface of the ternary positive electrode active material, thereby improving the discharge capacity, cycle stability and rate performance of the material; it can also replenish the consumption of lithium ions, passivate the SEI film, and isolate the direct contact between the positive electrode material and the electrolyte, thereby reducing the occurrence of side reactions and improving the long cycle performance of the material.
[0050] Therefore, the positive electrode material prepared by the preparation method provided in the embodiment of the present invention can effectively improve the problem that the positive electrode material of the existing ternary lithium-ion battery has poor structural stability, resulting in a short battery cycle life.
[0051] In the above step 201, the solvent may be ethanol and / or deionized water.
[0052] Optionally, in one embodiment, in the above step 201, the mass ratio of the sum of the masses of Li3PO4, B2O3 and LiF to the mass ratio of the ternary positive electrode active material is 0.5 to 3:100, so that the mass of the coating layer is 0.5% to 3% of the mass of the core ternary positive electrode active material, which can not only improve the ion conductivity of the material, but also improve the energy density of the battery. Optionally, the mass ratio of the sum of the masses of Li3PO4, B2O3 and LiF to the mass ratio of the ternary positive electrode active material can be any value of 0.5:100, 1:100, 2:100, 3:100, or a range of any two of the above.
[0053] Optionally, in one implementation, the above step 201 includes step 211:
[0054] Step 211: The ternary cathode active material is a ternary polycrystalline cathode material. After mixing the ternary polycrystalline cathode material with Li3PO4, B2O3, and LiF, the solvent is added, and optionally, it is crushed and then dried.
[0055] In this embodiment, the drying condition can specifically be vacuum drying.
[0056] In this embodiment, when the ternary cathode active material is a polycrystalline material, not only is the ternary polycrystalline cathode material mixed uniformly with Li3PO4, B2O3, and LiF by using the solvent, so that Li3PO4, B2O3, and LiF are uniformly distributed on the surface of the ternary cathode active material, forming a coating layer on the surface of the ternary polycrystalline active material; optionally, the polycrystalline structure can also be broken into a single crystal material structure through physical actions such as ball milling and grinding, thereby achieving the effect of in-situ single crystal coating.
[0057] Specifically, the coating materials Li3PO4, B2O3, and LiF and the ternary polycrystalline cathode material are added to the ball milling tank according to a mass ratio of 0.5~3:100, and then solvents such as anhydrous ethanol and deionized water are poured in according to a mass ratio of solvent:mixture = 1~5:1, and grinding media such as Zr2O3 balls are put in according to a mass ratio of grinding media:mixture = 5~9:1 for ball milling treatment, where a + b + c = 1, and 0 < a, b, c < 1, the ball milling speed can be 100 r / min~500 r / min, the ball milling time can be 0.5 h~5 h, and then the ball milled material is placed in an incubator at 60°C~100°C for vacuum drying for 2 h~10 h, and the coated single crystal cathode material can be obtained.
[0058] Optionally, in one embodiment, step 201 above includes step 212:
[0059] Step 212: The ternary cathode active material is a ternary single crystal cathode material. The ternary single crystal cathode material is added to a solvent at 60°C~100°C and treated for 0.5 h~5 h, and then dried to obtain the dried body.
[0060] In this embodiment, the drying method can specifically be drying in an oven.
[0061] In this embodiment, when the ternary cathode active material is a single crystal material, the ternary single crystal cathode material is directly mixed uniformly with Li3PO4, B2O3, and LiF by using the solvent, and Li3PO4, B2O3, and LiF can be uniformly distributed on the surface of the ternary cathode active material.
[0062] Among them, a water bath, an oil bath pot or a high-temperature magnetic stirrer is used to stir and heat the solvent, and then the coating materials Li3PO4, B2O3 and LiF and the ternary single-crystal cathode material are added to the solvent according to a mass ratio of 0.5-3:100 and stirred at a constant temperature. Among them, a + b + c = 1, and 0 < a, b, c < 1. The constant temperature can be 60°C - 100°C, the stirring speed can be 12 r / s - 16 r / s, and the stirring time can be 0.5 h - 5 h to obtain a gelatinous glassy material. Then, the gelatinous glassy material is placed in an incubator at 60°C - 100°C and dried for 2 h - 10 h to obtain the coated single-crystal cathode material.
[0063] In the above step 202, the protective gas can be an oxygen-free, air, high-oxygen atmosphere or an inert gas, such as N2.
[0064] Optionally, in one embodiment, in the above step 202, the sintering temperature is 300°C - 600°C and the time is 1 h - 10 h. Sintering under the above temperature and time conditions can cause Li3PO4, B2O3 and LiF to react and rearrange elements to generate 5% - 20% of LiBF4 and LiPF6 in the total amount of the coating agent.
[0065] Among them, under high-temperature melting conditions, Li3PO4, B2O3 and LiF react according to the following equation to generate LiBF4 and LiPF6:
[0066] B2O3 + Li3PO4 + 10LiF → LiBF4 + LiPF6 + LiB2O + 5Li2O.
[0067] Among them, LiBF4 and LiPF6 belong to two lithium salts of the lithium-ion battery electrolyte. As the coating layer of the cathode material, it is not only beneficial to the conduction of lithium ions, but also more suitable for the charge and discharge of the battery in a low-temperature environment, and can effectively improve the low-temperature performance of the lithium-ion battery.
[0068] In the embodiment of the present invention, the dried body can be placed in a muffle furnace or a tube furnace for the above sintering treatment.
[0069] In practical applications, when forming the coating, the content and thickness of the coating layer can be controlled by adjusting the mass ratio between the ternary cathode active material and the coating material. And the higher the concentration of the coating substance, the greater the mass ratio of the coating layer to the ternary cathode active material and the thicker the thickness of the coating layer.
[0070] Optionally, the particle size D50 of the ternary polycrystalline cathode material provided by the embodiment of the present invention is 5.0 μm - 15.0 μm, and the particle size D50 of the ternary single-crystal cathode material is 2.0 μm - 5.0 μm.
[0071] In the embodiment of the present invention, when the particle size D50 of the ternary single crystal positive electrode material is within the above range, the positive electrode material can have a suitable specific surface area, can reduce the occurrence of side reactions, reduce the amount of gas produced, and can also shorten the migration path of lithium ions, which is beneficial to improving the rate performance of the battery. Preferably, the D50 of the single crystal positive electrode material is 2.0μm to 4.0μm, for example, any value of 2.5μm, 3.0μm, 3.5μm, 4.0μm, or a range of any two of the above.
[0072] The above-mentioned single crystal positive electrode material is a spherical or quasi-spherical structure. In the actual preparation process, the above-mentioned single crystal positive electrode material with a D50 range of 2.0 μm to 5.0 μm can be obtained by changing the ball milling parameters. Specifically, the ball milling time, ball milling speed, etc. can be controlled.
[0073] The present invention also proposes a secondary battery, comprising a positive electrode plate, wherein the positive electrode plate comprises a positive electrode collector and a positive electrode active material layer arranged on the positive electrode collector, and the positive electrode active material layer comprises the positive electrode material as described above or the positive electrode material prepared by the above preparation method.
[0074] In some embodiments, the double-sided surface density of the positive electrode sheet is 350 g / m 2 ~400g / m 2 , for example, it can be 350g / m 2 , 360g / m 2 , 370g / m 2 , 380g / m 2 , 390g / m 2 When the surface density of the positive electrode sheet is within the above range, it can effectively take into account both rate performance and energy density and slow down polarization.
[0075] Optionally, in one embodiment, the positive electrode plate further includes a conductive agent and an adhesive, and the adhesive may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylic resin.
[0076] Optionally, in one embodiment, the conductive agent may be acetylene black, carbon fiber, carbon nanotube, Ketjen black, artificial graphite, natural graphite, hard carbon, soft carbon, carbon black, graphene, etc.
[0077] In some embodiments, the positive electrode sheet is prepared as follows: the components for preparing the positive electrode sheet, such as the positive electrode active material including the positive electrode material, the binder and any other components are dispersed in a solvent such as N-methylpyrrolidone to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector; after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0078] The secondary battery provided by the embodiment of the present invention further includes a negative electrode plate, a separator and an electrolyte.
[0079] Among them, the negative electrode plate includes a negative electrode collector and a negative electrode active material layer arranged on the above-mentioned negative electrode collector. The above-mentioned negative electrode active material layer can adopt negative electrode active materials for batteries known in the art, such as artificial graphite, natural graphite, hard carbon, soft carbon, carbon black, etc.
[0080] The electrolyte plays a role in conducting ions between the positive electrode and the negative electrode. In some embodiments, the electrolyte includes an electrolyte salt and a solvent, and the electrolyte salt is a lithium salt.
[0081] The embodiment of the present invention further provides an electric device, comprising the above-mentioned secondary battery, wherein the above-mentioned secondary battery is used as a power supply for the electric device.
[0082] For the above-mentioned secondary battery embodiments and electrical equipment embodiments, their positive electrode plates include a positive electrode active material layer, and the above-mentioned positive electrode active material layer includes the above-mentioned positive electrode material, and can achieve the same technical effects. In order to avoid repetition, they will not be described here. For relevant matters, please refer to the partial description of the positive electrode material embodiment.
[0083] In order to make the invention purpose, technical scheme and beneficial effect of the present invention clearer, the present invention is further described below in conjunction with embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.
[0084] The present invention is described in detail below by way of examples.
[0085] Test Method
[0086] (1) SEM scanning electron microscope test:
[0087] A thermal field emission ultra-high resolution scanning electron microscope, reference model Zeiss Ultra-55 from Germany, was used to observe the microscopic morphology of the samples at 1K\2K\5K\10K\20K\50K\100K.
[0088] (2) Discharge capacity and capacity retention rate test:
[0089] Perform an initial RPTS test to obtain the battery's capacity and initial DCIR information;
[0090] The initial discharge specific capacity is obtained by dividing the fractional capacity by the active material content;
[0091] The following electrochemical tests were performed according to the fractional capacity:
[0092] ① Constant current discharge: current 0.33C constant current discharge, lower limit voltage 2.8V;
[0093] ② Leave for 10 minutes;
[0094] ③ Constant current and constant voltage charging: current 0.33C, upper limit voltage 4.25V\4.30V\4.35V\4.40V\4.45V
[0095] \4.50V, cut-off current 0.05C;
[0096] ④ Leave for 10 minutes;
[0097] ⑤ Repeat the above steps 800 times;
[0098] ⑥Record the discharge capacity in the first week and the discharge capacity after 800 cycles.
[0099] Capacity retention rate = discharge capacity after cycle / discharge capacity in the first cycle*100%.
[0100] (3) DCIR growth test:
[0101] ① Under normal temperature of 25±5℃, adjust the battery SOC to 50%, charge at 0.33C constant current to U1 voltage, and then charge at U1 constant voltage until the current is less than 0.05C;
[0102] ②Stand still for 30 minutes, discharge at 0.33C until the capacity is 0.5 times the capacity;
[0103] ③Execute steps ①~② 600 times in a loop.
[0104] After each cycle, the battery was placed at room temperature for 2 hours, and the voltage V1 was recorded; the battery was discharged at a constant current of 1.5C for 30 seconds, and the voltage V2 was recorded; the battery was placed at room temperature for 10 minutes, and the voltage V3 was recorded; the battery was discharged at a constant current of 1.5C for 30 seconds, and the voltage V4 was recorded; the DCIR value was calculated using the following formula:
[0105] DCIR = (V1-V2) / specified current * 1000 (unit: mΩ)
[0106] DCIR charge = (V4-V3) / specified current * 1000 (unit: mΩ)
[0107] DCIR growth = (DCIR-DCIR initial) / DCIR initial * 100% (unit: %)
[0108] (4) 45℃ long cycle test:
[0109] The test temperature condition is 45℃±5℃. First, the RPTS test is performed at room temperature, and then the battery is charged to 4.35V at 1C constant current and constant voltage in a 45℃ constant temperature box, with a cut-off current of 0.05C and a 1C constant current discharge to 2.8V. The room temperature RPTS test is performed every 100 cycles, and the test is stopped when the capacity retention rate drops to 80%, and the number of cycles is recorded.
[0110] (5) 60℃ high temperature storage performance test:
[0111] Under the temperature condition of 25℃±5℃, the battery is subjected to RPTS test, placed at room temperature for 2h, and the initial voltage, thickness and weight are recorded. Placed in a 60℃ constant temperature box for 7\28\56\84D, the sample is taken out, and placed at room temperature for 6~8h to recover, and the termination voltage, thickness and weight are recorded. The sample is discharged, and the discharge capacity is recorded as the residual capacity. Then the RPTS test is performed, and the maximum discharge capacity is taken as the recovery capacity. After the storage of the last stage is completed, the termination RPTS test is performed.
[0112] Record the capacity and energy\voltage\thickness\weight data before and after storage, calculate the remaining capacity rate and recovery rate / voltage drop / DCIR change rate, etc. Calculate DCIR and power characteristics.
[0113] (6) Gas production test:
[0114] According to the Archimedes principle, the volume of the battery was tested using the Archimedes drainage method. Three sets of data were recorded in parallel for each test and the average value was taken.
[0115] ①45℃ cycle gas production volume test:
[0116] After each RPTS test, the battery volume was tested; the difference in volume before and after 200 cycles was recorded as the gas production volume of the battery after 200 cycles at 45°C;
[0117] ②45℃ storage gas production volume test:
[0118] After each RPTS test, the battery volume is tested; the difference in volume before and after storage is recorded as the gas production volume of the battery stored at 45°C for the corresponding time;
[0119] Example 1
[0120] (1) Preparation of positive electrode materials:
[0121] a. Weigh 4.8390g of LiNi 0.72 Co 0.05 Mn 0.23O2 ternary single crystal cathode material is used as the ternary cathode active material;
[0122] b. Weigh the coating agent according to the total mass of the coating agent being 1.5wt% of the mass of the ternary positive electrode active material, dissolve it in 20mL of deionized water, and then stir it at a constant temperature of 80°C at a constant speed of 15 r / s for 1h to obtain a coating solution; wherein the coating agent is a mixture of Li3PO4, B2O3, and LiF in a molar ratio of 0.15:0.15:0.7;
[0123] c. Slowly add the weighed ternary positive electrode active material into the coating solution, heat at 80°C until the solution evaporates, and then place in a drying oven at 80°C for 8 hours;
[0124] d. Take out the material, grind it evenly and place it in a corundum ark. After the grinding tool is compacted, place it in a tubular furnace and sinter it under a N2 atmosphere. The heating time during the sintering process is 2 hours, the sintering temperature is 550°C, and the sintering time is 5 hours. Cool it naturally to obtain the target material, grind it evenly, and sieve it with 200 mesh to obtain the positive electrode material of the ternary positive electrode active material coated with 0.15Li3PO4·0.15B2O3·0.7LiF.
[0125] (2) Preparation of positive electrode
[0126] The positive electrode material, conductive agent acetylene black (Super P) and binder polyvinylidene fluoride (PVDF) were mixed evenly at a mass ratio of positive electrode material: Super P: PVDF = 97:2:1, and evenly dispersed in 1-methyl-2-pyrrolidone (NMP) to form a uniform slurry. The mixed slurry was coated on both sides of the aluminum foil, and the surface density of the electrode was controlled to be 380g / m 2 After high-temperature drying, rolling, cutting and slitting, the positive electrode sheet is prepared.
[0127] (3) Preparation of negative electrode sheet
[0128] The negative electrode materials graphite, styrene-butadiene rubber (SBR), conductive carbon black and sodium carboxymethyl cellulose (CMC) are homogenized in a mass ratio of 50:1:1:1, and evenly coated on an aluminum foil. After high-temperature drying, the mixture is rolled, cut into pieces and stripped to prepare a negative electrode sheet.
[0129] (4) Preparation of lithium-ion batteries
[0130] The positive electrode, negative electrode and separator (PE separator) are wound and put into the shell, and the electrolyte (the electrolyte composition is a mixture of carbonate solvent and 1M LiPF6) is injected. After packaging, drying and chemical composition, the lithium-ion battery can be prepared.
[0131] Example 2
[0132] The difference between Example 2 and Example 1 is that in step (b), the coating agent is weighed so that the total mass of the coating agent is 0.5 wt % of the mass of the ternary positive electrode active material.
[0133] Example 3
[0134] The difference between Example 3 and Example 1 is that in step (b), the coating agent is weighed so that the total mass of the coating agent is 3 wt % of the mass of the ternary positive electrode active material.
[0135] Example 4
[0136] The difference between Example 4 and Example 1 is that in step (d), the sintering temperature is adjusted to 300° C. and the sintering time is adjusted to 1 hour.
[0137] Example 5
[0138] The difference between Example 5 and Example 1 is that in step (d), the sintering temperature is adjusted to 600° C. and the sintering time is adjusted to 10 h.
[0139] Example 6
[0140] The difference between Example 6 and Example 1 is that in step (b), the coating agent is a mixture of Li3PO4, B2O3, and LiF in a molar ratio of 0.8:0.1:0.1.
[0141] Example 7
[0142] The difference between Example 7 and Example 1 is that in step (b), the coating agent is a mixture of Li3PO4, B2O3, and LiF in a molar ratio of 0.1:0.8:0.1.
[0143] Example 8
[0144] The difference between Example 8 and Example 1 is that in step (b), the coating agent is a mixture of Li3PO4, B2O3, and LiF in a molar ratio of 0.1:0.1:0.8.
[0145] Example 9
[0146] The difference between Example 9 and Example 1 is that: in step (b), the coating agent is Li3PO4, B2O3, and LiF mixed in a molar ratio of 0.2:0.1:0.7;
[0147] In step (d), the sintering temperature is adjusted to 600°C.
[0148] Example 10
[0149] The difference between Example 10 and Example 1 is that: in step (a), the ternary single crystal positive electrode material is adjusted to a ternary polycrystalline positive electrode material;
[0150] In step (b), the deionized water is adjusted to a solvent in which anhydrous ethanol and deionized water are mixed in a volume ratio of 2:1;
[0151] In step (c), the weighed LiNi 0.72 Co 0.05 Mn 0.23 The O2 ternary positive electrode active material was slowly added to the coating solution, and the Zr2O3 ball was added according to the mass ratio of Zr2O3 ball: mixture = 8:1, and then ball-milled at a speed of 300r / min for 1 hour, heated at a constant temperature of 80°C until the solution evaporated, and then placed in a constant temperature box at 80°C for vacuum drying for 8 hours;
[0152] In step (d), the sintering temperature is adjusted to 600°C.
[0153] Embodiment 11
[0154] The difference between Example 11 and Example 1 is that in step (1), LiNi 0.72 Co 0.05 Mn 0.23 O2 adjusted to LiNi 0.8 Co 0.15 Al 0.05 O2.
[0155] Comparative Example 1
[0156] The difference between Comparative Example 1 and Example 1 is that in step (b), the coating agent is a mixture of Li3PO4 and B2O3 in a molar ratio of 0.15:0.15.
[0157] Comparative Example 2
[0158] The difference between Comparative Example 2 and Example 1 is that in step (b), the coating agent is a mixture of Li3PO4 and LiF in a molar ratio of 0.15:0.7.
[0159] Comparative Example 3
[0160] The difference between Comparative Example 3 and Example 1 is that in step (b), the coating agent is a mixture of B2O3 and LiF in a molar ratio of 0.15:0.7.
[0161] The coating content and the fluorine-containing lithium salt content in the coating layer in each embodiment and comparative example were tested, and the test data are shown in Table 1.
[0162] The positive electrode materials in Example 1, Examples 9-10 and Comparative Example 1 were subjected to SEM scanning electron microscope testing, and the test results were as follows: Figure 2-1 to Figure 2-4 As shown. Figure 2-1 to Figure 2-4It can be seen that the surface of the single crystal material of Example 1 is smooth, the amount of fine powder is relatively less, and the coating effect is the best; the particle size of the material of Example 9 is larger than that of the material of Example 1, and the amount of fine powder on the surface is relatively more; the material of Example 10 is obtained by in-situ coating of polycrystalline, and the uniformity of the particle size distribution of the material is relatively poor, and there is a phenomenon of small particle agglomeration. At the same time, the amount of fine powder on the surface is similar to that of Example 9; although the particle size of the material of Comparative Example 1 has large particles, the small particles are less agglomerated, and the amount of fine powder on the material surface is the largest, and black spots appear on the surface of the material.
[0163] The batteries prepared in each embodiment and comparative example were subjected to capacity retention test, DCIR growth test, long cycle test, discharge capacity test and high temperature storage performance test. The test data are shown in Table 2.
[0164] In addition, the batteries in Example 1, Examples 9-10 and Comparative Example 1 were subjected to a long cycle gas generation test. The test results are as follows: Figure 4 shown.
[0165] Table 1
[0166]
[0167] Table 2
[0168]
[0169] Comparison of 45°C long cycle capacity retention and DCIR growth test of the batteries in Example 1, Examples 9-10 and Comparative Example 1 Figure 3 shown; through Figure 3 It can be seen that the capacity retention rate of the material in Example 1 is the highest and the DCIR growth rate is the lowest, indicating that the coating effect of Example 1 is better, the coating layer is more uniform and more stable, and its coating scheme is the best among the four experiments; and because there are only two coating agents in Comparative Example 1, the improvement effect of its electrochemical performance is not obvious.
[0170] Comparison of long cycle gas generation test of the batteries in Example 1, Examples 9-10 and Comparative Example 1 Figure 4 shown; through Figure 4 It can be seen that the gas production volume of the battery of the coating scheme of Example 1 is the smallest, and the gas production volume of the overall embodiment is roughly smaller than the gas production volume of the battery of the coating scheme of the comparative example. The small gas production volume indicates that the interface of the material is more stable, indicating that the formed coating layer is more uniform and more stable, effectively inhibiting the side reaction between the material surface and the electrolyte, reducing the degree of electrolyte decomposition reaction, and effectively improving the chemical stability of the interface.
[0171] Comparison of discharge capacity of the batteries at different upper limit voltages at room temperature in Example 1, Examples 9-10 and Comparative Example 1 Figure 5 shown; through Figure 5It can be seen that the discharge capacities of Example 1, Example 9, and Example 10 are significantly better than those of Comparative Example 1, indicating that the coating layer formed by the solution of this embodiment is a more stable and uniform fast ion conductor coating layer. It not only helps the ion conduction of the positive electrode material, but also plays a positive role in the performance of the battery system as an electrolyte lithium salt, which is more conducive to the performance of the material's discharge capacity.
[0172] The comparison of the high-temperature storage performance tests of the batteries in Example 1, Examples 9-10, and Comparative Example 1 is as Figure 6 shown; through Figure 6 It can be seen that the gas production volume of the batteries in Example 1, Examples 9-10 at 60 °C during high-temperature storage is significantly smaller than that of the battery in Comparative Example 1 at 60 °C during high-temperature storage, indicating that the internal structure of the positive electrode material of the embodiments of the present invention is stable, the interface stability is good under high-temperature conditions, and it is not easy to have side reactions with the electrolyte, so the gas production is slower and less.
[0173] From Example 1-3 combined with Table 2, it can be seen that the content of the coating layer is directly related to the performance of the battery, and when the mass fraction of the coating layer in the ternary positive electrode active material is 1.5%, the comprehensive performance of the battery is better.
[0174] From Example 1, Examples 4-5 combined with Table 1 and Table 2, it can be seen that the sintering conditions are directly related to the coating effect and affect the content of the fluorinated lithium salt in the coating layer. Among them, when the content of the fluorinated lithium salt in the coating layer is 10 wt%, the comprehensive performance of the battery is better.
[0175] From Example 1, Examples 6-8 and Comparative Examples 1-3 combined with Table 1 and Table 2, it can be seen that the coating effect is affected by the ratio of the coating agent. When Li3PO4, B2O3, and LiF are added to the coating agent at the same time, the discharge capacity and cycle performance of the battery can be significantly improved.
[0176] In this application, the positive electrode material includes a core and a coating layer provided on the surface of the core. The core includes a ternary positive electrode active material, and the coating layer includes aLi3PO4·bB2O3·cLiF, where a + b + c = 1, and 0 < a, b, c < 1. Among them, using Li3PO4, B2O3, and LiF to adaptively coat the ternary positive electrode active material as the coating layer can not only form a fast ion conductor migration channel on the surface of the ternary positive electrode active material, thereby improving the discharge capacity, cycle stability, and rate performance of the material; it can also supplement the consumption of lithium ions, passivate the SEI film, and isolate the direct contact between the positive electrode material and the electrolyte, thereby reducing the occurrence of side reactions and improving the long-cycle performance of the material. Therefore, the positive electrode material provided by the embodiments of the present invention improves the problem that the structural stability of the positive electrode material of the existing ternary lithium-ion battery is poor, resulting in a short battery cycle life.
[0177] Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they are aware of the basic creative concept. Therefore, the claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the embodiments of the present invention.
[0178] The above is a detailed introduction to a positive electrode material and a preparation method thereof, a secondary battery and an electrical device provided by the present invention. Specific examples are used in this article to illustrate the principle and implementation mode of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for a general technician in this field, according to the idea of the present invention, there will be changes in the specific implementation mode and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.
Claims
1. A positive electrode material, characterized in that: The positive electrode material comprises a core and a coating layer arranged on the surface of the core, wherein the core comprises a ternary positive electrode active material, and the coating layer comprises aLi3PO4·bB2O3·cLiF, wherein a+b+c=1, and 0 <a、b、c<1;a:b:c=(1~10):(1~10):(1~10); The coating layer also includes a fluorine-containing lithium salt, and the fluorine-containing lithium salt includes LiBF4 and / or LiPF6; wherein the LiBF4 and / or LiPF6 are formed by element rearrangement of Li3PO4, B2O3 and LiF in the coating layer.
2. The positive electrode material according to claim 1, characterized in that The ternary positive electrode active material includes LiNi x Co y A z O2, wherein A is selected from one or more of Mn and Al, x+y+z=1, and 0 <x、y、z<1。 3. The positive electrode material according to claim 1, characterized in that The mass ratio of the coating layer to the core is 0.5-3:
100.
4. The positive electrode material according to claim 1, characterized in that The fluorine-containing lithium salt accounts for 5wt% to 20wt% of the total amount of the coating layer.
5. A method for preparing a positive electrode material, characterized in that: include: The ternary positive electrode active material is mixed with Li3PO4, B2O3 and LiF in a solvent and then dried to obtain a dry body; wherein the molar ratio of Li3PO4, B2O3 and LiF is 0~1:0~1:0~1; Sintering the dried body in a protective gas atmosphere to obtain a positive electrode material; the protective gas is an oxygen-free or inert gas; The sintering temperature is 300° C. to 600° C., and the sintering time is 1 h to 10 h.
6. The preparation method according to claim 5, characterized in that: The ternary positive electrode active material is uniformly mixed with Li3PO4, B2O3 and LiF in a solvent and then dried, including: The ternary positive electrode active material is a ternary polycrystalline positive electrode material. The ternary polycrystalline positive electrode material is mixed with Li3PO4, B2O3 and LiF, and then the solvent is added, and then the drying process is performed.
7. The preparation method according to claim 5, characterized in that: The ternary positive electrode active material is uniformly mixed with Li3PO4, B2O3 and LiF in a solvent and then dried, including: The ternary positive electrode active material is a ternary polycrystalline positive electrode material. The ternary polycrystalline positive electrode material is mixed with Li3PO4, B2O3 and LiF, and then the solvent is added, crushed and then dried.
8. The preparation method according to claim 7, characterized in that: The particle size D50 of the ternary polycrystalline positive electrode material is 5.0 μm to 15.0 μm.
9. The preparation method according to claim 5, characterized in that: The ternary positive electrode active material is uniformly mixed with Li3PO4, B2O3 and LiF in a solvent and then dried, including: The ternary positive electrode active material is a ternary single crystal positive electrode material. The ternary single crystal positive electrode material and Li3PO4, B2O3, and LiF are added to a solvent at 60°C to 100°C for treatment for 0.5h to 5h, and then the drying treatment is performed.
10. The method for preparing the positive electrode material according to claim 5, characterized in that: The temperature of the drying treatment is 60° C. to 100° C., and the time of the drying treatment is 2 h to 10 h.
11. The preparation method according to claim 9, characterized in that: The particle size D50 of the ternary single crystal positive electrode material is 2.0 μm to 5.0 μm.
12. A secondary battery, characterized in that: The invention comprises a positive electrode plate, wherein the positive electrode plate comprises a positive electrode current collector and a positive electrode active material layer arranged on the positive electrode current collector, wherein the positive electrode active material layer comprises the positive electrode material according to any one of claims 1 to 4 or the positive electrode material prepared by the preparation method according to any one of claims 5 to 11.
13. An electrical equipment, characterized in that: The secondary battery according to claim 12 is included, and the secondary battery is used as a power supply for the electrical equipment.
Citation Information
Patent Citations
A method for reduce that residual alkali on the surface of high nickel material
CN109065857A
Lithium battery core-shell positive electrode material, lithium battery containing lithium battery core-shell positive electrode material and preparation method of lithium battery
CN113871588A
Positive electrode material, preparation method thereof and battery
CN116014094A